Treatment of Preschool Children With Autism Spectrum Disorder: A Trial to Evaluate a Learning Style Profile Intervention Program in China - Ma, Chen-huan; Chen, Ling-yan; Li, Meng-fan; Wu, Dan; Wang, Sha-sha; Zhao, Yan-jun; Shi, Jian-li; Rydell, Patrick J.; Chen, Jin-jin; Wang, Yu (Frontiers in Pediatrics, 2022)
Objective: To investigate whether the provision of LSP training improves development in preschool children with ASD in China and to describe the characteristics of children who benefit from the intervention. Methods: Eighty-one children aged 36 to 72 months diagnosed with ASD for the first time were recruited for the intervention group. All of them received 24 weeks of LSP training. Twenty-one children with ASD of the same age in the control group had never received any intervention after diagnosis but underwent an assessment. Assessments were conducted at baseline and 24 weeks later. Differences in the developmental level and severity of ASD symptoms over time and between groups were analyzed. Secondary analyses examined age effects among the 36–48-month, 48–60-month and 60–72-month age groups. Results: Within-group comparison of the intervention group revealed significant treatment effects after the intervention, according to: language, social and adaptive developmental quotients (DQs) of the China Developmental Scale; total Childhood Autism Rating Scale (CARS) score; and hyperactivity, peer problems, total difficulties and prosocial behavior scores of the Strengths and Difficulties Questionnaire (SDQ). Similar gains were observed in gross and fine motor DQs of the China Developmental Scale and emotional symptoms and conduct problems scores of the SDQ; however, the differences between these pre- and postintervention scores did not reach statistical significance. Comparisons among the three age groups in the intervention groups demonstrated a significant age effect on adaptive DQs of the China Developmental Scale; total CARS score; hyperactivity, peer problems and total difficulties scores of the SDQ. Comparison between the intervention and control groups revealed significant treatment effects on language, social and adaptive DQs of the China Developmental Scale; total CARS score; and emotional symptoms, conduct problems, hyperactivity, peer problems, total difficulties and prosocial behavior scores of the SDQ after the intervention. Similar gains were observed in gross and fine motor DQs of the China Developmental Scale, although differences between the two groups did not reach statistical significance. Conclusion: Our findings suggest that LSP can effectively improve social behavior and reduce severity of ASD symptoms in children with ASD. Our data also highlight the importance of early intervention.